Utilization of Silicone Sheet as a Protective Guide During Transoral Robotic Tongue Base Surgery. Issue 4 (October 2021) - Volner, Keith; Mostales, Joshua C.; Schoppy, David; Lim, Jae H.
This article presents a simple technique where a silicone sheet is used during transoral robotic surgery (TORS) to protect the upper airway structures from thermal damage during a base of tongue procedure. We review 10 cases of TORS tongue base reduction with the use of this technique, with no complications and with reduction of thermal damage to the lingual epiglottis and surrounding pharyngeal wall. Furthermore, it served as a guide during tongue base dissection to provide visual and tactile feedback to the inferior limit of resection, as well as to protect the endotracheal tube. The silicone sheet is an ideal material for use as a thermal barrier due to its widespread availability, intrinsic thermal properties, and translucency. The technique of using the silicone sheet is easy to implement and may prove useful to many transoral robotic surgeons, especially for newly trained TORS users and trainees.